PENGARUH BIMBINGAN PRANIKAH TERHADAP KEHARMONISAN RUMAH TANGGA DI KUA KECAMATAN GUNUNGPUYUH - Hilman Taufiq, Muhammad; Nurdin, Dede; Fuji hakiki, Muhamad (Wasīlah: Journal Of Sharia Sciences, 2026)
Premarital guidance is a preventive and strategic effort to equip prospective couples with knowledge, skills, and understanding to face the challenges of married life. This program aims to establish harmonious and sustainable families that are in accordance with the values of sakinah, mawaddah, and rahmah. This study aims to analyze the effect of premarital guidance on marital harmony. The research was conducted at the Office of Religious Affairs (KUA) of Gunungpuyuh District, Sukabumi City, involving 112 respondents. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to respondents and analyzed using IBM SPSS Statistics version 26. The results of the study indicate that premarital guidance has a positive effect on marital harmony (t = 8.519; p = 0.000). The study concludes that premarital guidance has a positive and significant effect on marital harmony; therefore, the research hypothesis is accepted. These findings reinforce the government’s objective of fostering strong and harmonious family life and support previous studies emphasizing the importance of premarital preparation in establishing families characterized by sakinah, mawaddah, and rahmah.